Representatives of the Gastrocopta gemina S t e k l o v group (Mollusca, Pulmonata) in the Neogene of Ukraine and Kazakhstan - Prysiazhniuk, V.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The terrestrial mollusks common for the continental deposits of the China and the Eastern Siberia were found in the Neogene deposits of Ukraine (the lower Sarmatian and the Pontian) and Kazakhstan. A new species of Gastrocopta borysthaenica from the Lower Sarmatian and a new subspecies of G. borysthaenica kurtschaense in the Pontian of Ukraine, as well as G. carnasa Y u n t o n g from the Kedeyskian suite of Kazakhstan, are described.